2014
DOI: 10.4103/0973-1296.131031
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect and mechanism of Ginkgo biloba extract-EGb 761 on STZ-induced diabetic cardiomyopathy in rats

Abstract: Diabetes mellitus (DM) is a complex metabolic disorder which leads to development of various long-term complications including cardiomyopathy. Oxidative stress due to hyperglycemia plays a key role in the development and progression of diabetic cardiomyopathy (DC). Oxidative stress causes the opening of mitochondrial permeability transition pore (mPTP) eventually leading to myocardium dysfunction. The Ginkgo biloba extract (EGb 761) has antioxidant and mitochondrial membrane potential stabilizing property. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…BB is one of the effective active components of EGb 761. To our knowledge, EGb 761 suppressed diabetic cardiac dysfunction in DM (Saini, Taliyan, & Sharma, ). Furthermore, EGb 761 had a vital effect in inducing insulin secretion and raising plasma insulin levels, which were responsive to oral glucose intake (Lim et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…BB is one of the effective active components of EGb 761. To our knowledge, EGb 761 suppressed diabetic cardiac dysfunction in DM (Saini, Taliyan, & Sharma, ). Furthermore, EGb 761 had a vital effect in inducing insulin secretion and raising plasma insulin levels, which were responsive to oral glucose intake (Lim et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…For example, the hyperglycemia (Fig. 2B) induction of osmotic diuresis (Abe et al, 2002), and oxidative stress (Saini et al, 2014), which suppresses myocardial function in STZ rats (Table 2), might ultimately, lower BP. By contrast, the sympathoexcitation caused by hyperglycemia-evoked neuronal oxidative stress (Patel et al, 2011), and the baroreflex dysfunction shown here (Table 2) and in some (Milan et al, 2007), but not in other (Patel and Zhang, 1995) studies, might tip the balance towards the slight elevation in BP in STZ rats (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…PKR is activated through autophosphorylation and once activated it phosphorylates certain substrates including the α-subunit of eukaryotic initiation factor 2 [6,8]. PKR has also been reported to be activated by cellular stress, oxidative stress, metabolic stress, and inflammation [6,9,10,11] and these stress signals have also been observed under diabetic and vascular complications [12]. The PKR signaling pathway may therefore be an attractive target for the development of anti-diabetic and cardioprotective drugs.…”
Section: Introductionmentioning
confidence: 99%